The Women Employees within the Frame of Social Responsibility and an Analyse - Cagiran Kendirli, Hulya; Gulen, Tugba; Kumbul, Tugba (Journal of Economic Development, Environment and People, 2015)
Abstract: In many resources, corporate social responsibility is defined as an organization's ethic and responsible attitude towards all the partners in and outside of the instruction, it’s taking the decisions accordingly and apply them. In the researches that have been carried out recently, the concept of "partner" stands out. Institutions have relations with some certain partners such as consumers, advertisers and workers and so on as these groups include women as well. That is the reason why the studies should be carried out considering the women. This concept has a great role in increasing the number of the social responsibility projects of the institutions that put emphasize on women. Although Turkey signed CEDAW (Committee on the Elimination of Discrimination against Women) which is a legally binding contract and many contracts of ILO which aimed at protecting the equality of men and women, and made some certain laws to protect the equality, it was the 126th country of 130 countries according to the Index of Gender Mainstreaming report published by WEF (World Economic Forum) in 2013. In this regard, the need to replace women in the centre of social responsibility projects is inevitable.